In Search of the Emotional Face: Anger Versus Happiness Superiority in Visual Search - Savage, R.; Lipp, Ottmar; Craig, B.; Becker, S.; Horstmann, G. (American Psychological Association, 2013)
Previous research has provided inconsistent results regarding visual search for emotional faces, yielding evidence for either anger superiority (i.e., more efficient search for angry faces) or happiness superiority effects (i.e., more efficient search for happy faces), suggesting that these results do not reflect on emotional expression, but on emotion (un-)related low-level perceptual features. The present study investigated possible factors mediating anger/happiness superiority effects; specifically search strategy(fixed vs. variable target search; Experiment 1), stimulus choice (Nimstim database vs. Ekman & Friesen database; Experiments 1 and 2), and emotional intensity (Experiment 3 and 3a). Angry faces were found faster than happy faces regardless of search strategy using faces from the Nimstim database (Experiment 1). By contrast, a happiness superiority effect was evident in Experiment 2 when using faces from the Ekman and Friesen database. Experiment 3 employed angry, happy, and exuberant expressions (Nimstim database) and yielded anger and happiness superiority effects, respectively, highlighting the importance of the choice of stimulus materials. Ratings of the stimulus materials collected in Experiment 3a indicate that differences in perceived emotional intensity, pleasantness, or arousal do not account for differences in search efficiency. Across three studies, the current investigation indicates that prior reports of anger or happiness superiority effects in visual search are likely to reflect on low-level visual features associated with the stimulus materials used, rather than on emotion.